The myth of equality : uncovering the roots of injustice and privilege - Wytsma, Ken (Downers Grove, Illinois : IVP Books, an imprint of InterVarsity Press, 2017)
It's clear that issues of race and equality have come to the forefront in our nation's consciousness. Every week yet another incident involving racial tension splashes across headlines and dominates our news feeds. But it's not easy to unpack the origins of these tensions, and perhaps we wonder whether any of these issues really has anything to do with us. Ken Wytsma, founder of the Justice Conference, understands these questions. He has gone through his own journey of understanding the underpinnings of inequality and privilege. In this timely, insightful book Wytsma unpacks what we need to know to be grounded in conversations about today's race-related issues. And he helps us come to a deeper understanding of both the origins of these issues and the reconciling role we are called to play as witnesses of the gospel. Inequality and privilege are real. The Myth of Equality opens our eyes to realities we may have never realized were present in our society and world. And we will be changed for the better as a result. - from publisher.
The story of race -- America's white standard: a nation of (European) immigrants -- When the world became racist: color in the western tradition -- Stolen labor -- How our cities got their shape: the great migration, redlining, and the roots of modern segregation -- Equality and the kingdom of God -- The aristocratic itch -- Does justice belong in our gospel conversation? -- The salvation industrial complex -- A short look at American individualism -- The challenge of privilege -- When racism went underground: implicit racial bias and the stories that hide within us -- The voice of justice -- Finding ourselves in the other.
Includes bibliographical references and index.
Keywords: Christianity and justice; Racism -- United States; Equality -- Religious aspects -- Christianity